1996
DOI: 10.1002/(sici)1099-1344(199602)38:2<105::aid-jlcr821>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific synthesis of tetradeuterated (R)- and (S)-ifosfamide

Abstract: SummaryThe tetradeuterated analogues of (R)-and (S)-ifosfamide [(S)-and (R)-2-(2-chloro-2,2-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It has been reported that 4‐OH‐CP exists as two tautomeric forms in solution, the ring‐opened aldehyde form (aldophosphamide or aldo P) and the ring‐closed form (4‐OH‐CP) 9, 17. In solution, it has been shown that aldo P readily undergoes β ‐elimination to eliminate acrolein (CH 2 CHCHO) to form PM 8, 16. The MS 2 spectrum (Table 1) of the MH + ion of 4‐OH‐CP/aldo P at m/z 277 shows the most abundant fragment ion at m/z 221.0, a loss of 56 Da corresponding to acrolein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 4‐OH‐CP exists as two tautomeric forms in solution, the ring‐opened aldehyde form (aldophosphamide or aldo P) and the ring‐closed form (4‐OH‐CP) 9, 17. In solution, it has been shown that aldo P readily undergoes β ‐elimination to eliminate acrolein (CH 2 CHCHO) to form PM 8, 16. The MS 2 spectrum (Table 1) of the MH + ion of 4‐OH‐CP/aldo P at m/z 277 shows the most abundant fragment ion at m/z 221.0, a loss of 56 Da corresponding to acrolein.…”
Section: Resultsmentioning
confidence: 99%
“…CP ( 1 ) and IF ( 2 ) were provided by the U.S. National Cancer Institute, and compounds 3 and 4 and all deuterium‐labeled compounds ( 1a , 1b , 2a and 5 , Scheme ) were synthesized as described 8. Compounds 3a and 4a were generated in situ from 3 and 4 , respectively, in the reaction medium.…”
Section: Methodsmentioning
confidence: 99%
“…The triphenylmethyl (trityl) group is a useful protecting group for primary amines that can be easily and quantitatively removed using 1N–6N aqueous HCl and as such was suitable for our research needs. A search of the literature revealed no reports of N 1 ‐tritylethane‐1,1,2,2‐ d 4 ‐1,2‐diamine, but the di‐deuterated analog 2‐(tritylamino)ethan‐ 1 , 1‐d 2 ‐ol has been previously reported . That material was synthesized in two steps by the reaction of trityl chloride with ethyl glycine ester hydrochloride, followed by reduction of the ester carbonyl with lithium aluminum deuteride.…”
Section: Resultsmentioning
confidence: 99%
“…(R)-IFA and (S )-IFA, (R)-and (S )-6,6,2 0 ,2 0 -tetradeuterioIFA [(R)-and (S)-IFA-d 4 ] were synthesized in Dr. Chan's laboratory (Wang and Chan 1996). Both chemical and isotopic purities were >99.5% as determined by GC/MS analysis.…”
Section: Chemicalsmentioning
confidence: 99%